(untitled) (TEST Ticontre. Theory Text Translation, 2015)
Sophocles’ Antigone can be considered as an example of the major problems a translator of the classics has to face. On the level of the language, dialogues and discourses conceived to persuade alternate with songs, choral and monodic, composed by association of images and played on emotions. Many authoritative translations have privileged the pain and the love present in the character of Antigone, obscuring however the powerful dramatic theme – the philia – the bounds on which public life is based, and which are differently understood by Antigone and Creon. This work tries to bring the attention back to the relation between the translation and the contents of the dramatic thought, and to the necessity of first of all restoring the literal meaning of the ancient texts, without obfuscating it with empty academic exercises.